Interoception: the forgotten modality in perceptual grounding of abstract and concrete concepts. (5th August 2018) - Connell, Louise; Lynott, Dermot; Banks, Briony
Abstract : Conceptual representations are perceptually grounded, but when investigating which perceptual modalities are involved, researchers have typically restricted their consideration to vision, touch, hearing, taste and smell. However, there is another major modality of perceptual information that is distinct from these traditional five senses; that is, interoception, or sensations inside the body. In this paper, we use megastudy data (modality-specific ratings of perceptual strength for over 32 000 words) to explore how interoceptive information contributes to the perceptual grounding of abstract and concrete concepts. We report how interoceptive strength captures a distinct form of perceptual experience across the abstract–concrete spectrum, but is markedly more important to abstract concepts (e.g. hungry, serenity ) than to concrete concepts (e.g. capacity, rainy ). In particular, interoception dominates emotion concepts, especially negative emotions relating to fear and sadness, moreso than other concepts of equivalent abstractness and valence. Finally, we examine whether interoceptive strength represents valuable information in conceptual content by investigating its role in concreteness effects in word recognition, and find that it enhances semantic facilitation over and above the traditional five sensory modalities. Overall, these findings suggest that interoception has comparable status to other modalities in contributing to the perceptual grounding of abstract and concrete concepts. This article is part of the theme issue 'Varieties of abstract concepts: development, use and representation in the brain'.